"المعالجة المحاسبية للمخزونات وفق النظام المحاسبي المالي CERAM BEN دراسة حالة لمؤسسة " - البشير, بن عمر; مصعب, هنيات; علي, بلي (جامعة الوادي - University of Eloued, 2023)
تعتمد المؤسسة سواء كانت إنتاجية أو تجارية بصورة كبير على أصولها وبشكل خاص المخزونات، فتمنحها أهمية بالغة خصوصا مع كبر حجمها وتفرعها، وذلك من أجل الحفاظ على بقائها واستمرارها، وهذا ما أدى بالنظام المحاسبي المالي لتحليل مختلف المشاكل التي تواجه المحاسب عند تسجيله عمليات شراء وبيع المخزونات وحتى جردها في نهاية السنة، وأدرج حلول تساعد في عملية الجرد والتسجيل المحاسبي بشكل كبير، وعليه يتوجب على المؤسسة اختيار طرق وأساليب للمعالجة والتقييم المحاسبي للمخزونات تتناسب مع طبيعة المؤسسة، ومن خلال تطبيق النظام المحاسبي المالي، يمكن لمحاسبة المخزونات أن تساهم في الحصول على قوائم مالية تبين الوضعية المالية للمؤسسة بصورة واضحة The establishment, whether productive or commercial, relies heavily on its assets, especially stocks, giving it great importance, especially with its large size and branching, in order to preserve its survival and continuity, and this is what led the financial accounting system to analyze the various problems facing the accountant when recording the purchase and sale of stocks Even its inventory at the end of the year, and solutions were included that greatly assist in the process of inventory and accounting registration, and accordingly the institution must choose methods and methods for accounting treatment and evaluation of inventories commensurate with the nature of the institution, and through the application of the financial accounting system, inventory accounting can contribute to obtaining financial statements Clearly shows the financial position of the institution
Keywords: المعالجة المحاسبية، المخزونات، النظام المحاسبي المالي .; Accounting treatment, inventories, financial accounting system.